Repurposing Therapeutics for Potential Treatment of SARS-CoV-2: A Review - Jennifer Santos (Viruses, 2020)
The need for proven disease-specific treatments for the novel pandemic coronavirus SARS-CoV-2 necessitates a worldwide search for therapeutic options. Since the SARS-CoV-2 virus shares extensive homology with SARS-CoV and MERS-CoV, effective therapies for SARS-CoV and MERS-CoV may also have therapeutic potential for the current COVID-19 outbreak. To identify therapeutics that might be repositioned for treatment of the SARS-CoV-2 disease COVID-19, we strategically reviewed the literature to identify existing therapeutics with evidence of efficacy for the treatment of the three coronaviruses that cause severe respiratory illness (SARS-CoV, MERS-CoV, and SARS-CoV-2). Mechanistic and in vitro analyses suggest multiple promising therapeutic options with potential for repurposing to treat patients with COVID-19. Therapeutics with particularly high potential efficacy for repurposing include camostat mesylate, remdesivir, favipiravir, tocilizumab, baricitinib, convalescent plasma, and humanized monoclonal antibodies. Camostat mesylate has shown therapeutic potential, likely by preventing viral entry into epithelial cells. In early research, the targeted antivirals remdesivir and favipiravir appear to benefit patients by decreasing viral replication; clinical trials suggest that remdesivir speeds recovery from COVID-19. Tocilizumab and baricitinib appear to improve mortality by preventing a severe cytokine storm. Convalescent plasma and humanized monoclonal antibodies offer passive immunity and decreased recovery time. This review highlights potential therapeutic options that may be repurposed to treat COVID-19 and suggests opportunities for further research.